Pentingnya Kecerdasan Spiritual bagi Self-Regulated Learning Siswa SMA - Fifi Indrayani; Yuzarion Yuzarion; Nurul Hidayah (Jurnal Studia Insania, 2021)
Self-regulated learning is important for students for the optimal learning process and learning goals. This study aims to test empirically how spiritual intelligence predicts self-regulated learning in high school students in the city of North Maluku using linear regression techniques to 123 participants selected based on purposive random sampling, the measurement was carried out using 20 items on the spiritual intelligence scale (Cronbach α coefficient = 0.83. ) and 22 items on the scale of self-regulated learning g (Cronbach's α coefficient = 0.96) The results of data analysis show that the regression coefficient (t) is 15.422 with a significance level of 0.000 (p <0.05), which means that spiritual intelligence can predict self-regulated learning for high school students with an effective contribution of 88.4%. percent. Self-regulated learning is important for students for the optimal learning process and learning goals. This study aims to test empirically how spiritual intelligence predicts self-regulated learning in high school students in the city of North Maluku using linear regression techniques to 123 participants selected based on purposive random sampling, the measurement was carried out using 20 items on the spiritual intelligence scale (Cronbach α coefficient = 0.83. ) and 22 items on the scale of self-regulated learning g (Cronbach's α coefficient = 0.96) The results of data analysis show that the regression coefficient (t) is 15.422 with a significance level of 0.000 (p <0.05), which means that spiritual intelligence can predict self-regulated learning for high school students with an effective contribution of 88.4%. percent.